Effect of stage of growth and sampling procedure on the trace mineral content of Kansas native grass - Arthington, J.D.; Corah, L.R.; Utter, S.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To determine the trace mineral content of Kansas native grasses, samples were collected from four locations of tall or intermediate grasses and four locations of short grasses. Copper (Cu) and zinc (Zn) levels tended to be lower during dormancy than in the growing season; however, manganese (Mg) and iron (Fe) levels were essentially the same throughout the year. In terms of meeting the dietary requirements of grazing cattle, Cu was adequate in June but marginal in February, whereas Zn was marginal to deficient at both collection times. In addition, the impact of grazing selectivity on the validity of trace mineral analysis of hand-clipped pasture samples was evaluated. Although samples collected via rumen cannulae from grazing steers contained higher (P<.01) levels of protein, calcium, and phosphorus than comparable hand-clipped samples, no differences occurred in the trace mineral contents.
Keywords: Beef; Trace mineral; Grazing selectivity; Native grass